Physical Activity and Psychological Well-Being in the Adult Population During the COVID-19 Pandemic: A Systematic Review (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2023)
The COVID-19 pandemic has become a global crisis that has caused various impacts on the psychological well-being and physical activity of the community. Correspondingly, physical activity is known to have a relationship and affect psychological well-being. Therefore, this study aimed to obtain a comprehensive picture of the level and impact of the activity on psychological well-being in the adult population as well as recommendations for physical activity that could be done to improve psychological well-being during the COVID-19 pandemic. The research method used was a systematic literature review with the PRISMA (Preferred Reporting Item for Systematic Review and Meta-Analytic) analysis method. Search literature on the EBSCOhost, ProQuest, and ScienceDirect databases. Literature searches were limited to research articles published between January 1, 2020, to May 20, 2021. The initial search yielded 5,136 articles and finally found 15 articles that met the criteria. The results of the review revealed that during the COVID-19 pandemic, there was a decrease in the level of physical activity and psychological well-being, especially in the adult population, especially women and young adult groups. In addition, it was found that physical activity was either directly or indirectly associated with symptoms of depression, stress, anxiety, and positive feelings and emotions. Physical activity with moderate intensity has the most significant influence on psychological well-being. The forms of activity included lifting weights, yoga, double tennis, aerobics, muscle fitness, and explosive fitness. Based on this, it is certain that physical activity with moderate intensity has the most significant impact on psychological well-being, especially in increasing positive feelings and emotions and reducing depression, stress, and anxiety in adults.